EFEKTIVITAS PENERAPAN RENUNGAN DAN BACAAN KITAB SUCI BAGI ANGGOTA YUNIOR ALMA PUTERI DI BHAKTI LUHUR MALANG - Maria Vianti Desa; Rosalina Sirken (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2021)
The five points of spiritual life are the basis of ALMA PUTERI's spiritual life which have been applied since the initial training period, namely the aspirants, postulants and novices. The goal is to develop a deep spiritual life that is focused on surrender and pure devotion to Christ in the fellowship of ALMA PUTERI. Meditation and Bible Reading are included in the daily activities in spiritual formation, which are continuously improved so that they take root in ALMA PUTERI Junior members. The purpose of this study is to describe the application of reflection and reading of the Bible for ALMA PUTERI Junior members, as well as examine the extent to which the ALMA PUTERI Junior members are active in applying meditation and Bible reading. This type of research is descriptive qualitative. The data obtained in this study were based on the results of interviews, observations and documentation of the 5 main informants of the ALMA PUTERI Junior members and 3 additional informants in charge of the guesthouse. The results of the study show that the application of meditation is less effective, while the application of reading scriptures is effective for the development of the spiritual life of ALMA PUTERI Junior members in the Dieng Bhakti Luhur Complex, Malang.